PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP KETRAMPILAN BERBICARA DI KELAS V SEKOLAH DASAR - Agustinus Suban Molan; Maria Finsensia Ansel; Finsensius Mbabho (Program Studi PGSD Universitas Flores, 2020)
The purpose of this study was to determine the effect of cooperative learning model talking stick type on the speaking skills of fifth grade elementary school students in Indonesian. The type of research used is experimental research. The experimental research used was quasi experimental where there were two groups used, namely the experimental group and the control group. The experimental research used was quasi experimental where there were two groups used, namely the experimental group and the control group. The research approach is a quantitative approach. This research was conducted at SDN Riangkoli, East Flores Regency. The subjects in this study were all students in grade 5, totaling 26 people, which were divided into two groups, namely the experimental group amounting to 13 and the control group totaling 13 people. Data collection using tests and documentation. The data obtained from the research results will be analyzed using statistics, namely one-way ANOVA. The results of the data analysis of the pretest and posttest values in the experimental group or groups that applied the talking stick learning model and the control group or groups that applied the learning model obtained the pre-test scores of the experimental group or applying the talking stick type cooperative learning model. The average or mean is 54.62 and for the post-test value the average value is 84.15. Meanwhile, for the control class or conventional learning model for the pretest, an average value of 58.15 was obtained and the post-test obtained an average value of 72.46. This shows that there is a difference in the mean value of the experimental class and the control class seen from the pre-test and post-test scores. The result of the data analysis of hypothesis testing are the sign=0.000<0.05 at the significant level (alpha=0.05). This means that the effect of the talking stick type cooperative learning model is higher than the conventional learning model in Indonesian class V SDN Riangkoli.